Plyometric training programs in handball: A systematic scoping review - Rocha Henrique, J.; Ramirez-Campillo, R.; Afonso, J.; Miguel Silva, R.; Moran, J.; Manuel Clemente, F. (Kinesiology, 2023)
This systematic scoping review aimed to comprehensively identify and analyze the available evidence pertaining to the effects of plyometric training interventions on handball players. The search for relevant literature was conducted across prominent databases, including PubMed, Scopus, SPORTDiscus, and Web of Science Core Collection. The eligibility criteria focused on healthy handball players, without restrictions on age, sex, or competitive level, who were exposed to plyometric training interventions, either alone or in combination with other training methods. A meticulous screening process was conducted, whereby 3,195 titles were carefully evaluated, resulting in the inclusion of 35 eligible studies in this systematic scoping review, involving a total of 891 participants. Most studies on plyometric training in handball focused on indoor settings, conducted during the in-season period, and involved tier two athletes. The training frequency typically ranged from twice per week, with a duration of between 5 and 12 weeks, and incorporated some form of progressive overload. The number of total floor contacts varied between 20 and 600. There was a considerable variation in outcomes across the included studies, but most of them demonstrated a positive impact of plyometric training on improving jumping ability, sprinting speed, change of direction, strength, and balance. In conclusion, the predominant focus of the studies was on the lower limb, specifically aiming to assess the intervention influence on variables associated with strength and power. Notably, these investigations consistently highlighted favorable effects on enhancing these parameters among handball players. However, further research is needed to explore the effects of plyometric training in handball, particularly regarding exercise selection, optimal volume and intensity, rest intervals, and tapering protocols.